Glioma-Neuronal Interactions: A Study of Tumor Integration and Synaptogenesis Mediated Language Plasticity in Adult High-Grade Glioma. (16th November 2020) - Krishna, Saritha; Lee, Anthony T; Kakaizada, Sofia; Seo, Kyounghee; Raleigh, David R; Almeida, Nyle; Brang, David; Nagarajan, Srikantan S; Berger, Mitchel S; Monje, Michelle; Hervey-Jumper, Shawn L
Abstract: INTRODUCTION: Little is known about the mechanisms by which gliomas integrate into functional neural networks and influence complex cognitive processes such as language. Glioma-neuron interactions are bidirectional, with increased neuronal activity promoting tumor growth and the latter in turn influencing neuronal excitability and synaptic connections. It remains unknown whether glioma-neuron interactions play a role in maintaining long-range neural networks subserving cognition in humans. METHODS: We employed magnetoencephalography imaginary coherence measures of long-range FC to identify intratumoral high (HFC) and low (LFC) functional connectivity network hubs in patients with dominant temporal GBM. Primary patient samples and cultures from HFC and LFC sites were assessed for pre and post-synaptic marker expression, cocultured with murine hippocampal neurons, and induced neuron organoids. Secreted proteins were measured from patient serum and hippocampal neuron condition media. Language assessments were performed in addition to overall survival. RESULTS: Primary patient samples from HFC regions are enriched for glioblastoma cells with a synaptogenic profile as characterized by pre- and post-synaptic marker expression at both tissue and cellular level (coculture with mouse hippocampal neuron organoid models). RNA sequencing and proteomic analyses from HFC samples revealed a neurogenic signature including TSP1. Overexpression of TSP1 in LFC primary patient cultures rescues the synaptogenic and proliferative phenotype. Glioma integration as determined by intratumoral HFC negatively influenced patient overall survival and language processing. CONCLUSION: Glioma-neuron interactions are enriched within intratumoral high network connectivity regions. Glioma-induced neuronal synaptogenesis mediated by TSP1 contributes to the microenvironment in support of tumor network integration which negatively impacts behavior and survival.